Optimization and evaluation of the thermal treatment of canned green beans in brine - Condori, Moisés (2012)
It was determined the parameters of thermal treatment for the maximum retention of color (5,83 %) and texture (2,29 %) of canned green beans (Vicia faba L.) in brine, to processing temperature 126,7 °C for a time of 8,69 minutes, by Jen et al method. The tests were made with green beans from Mantaro valley, in Peru. Likewise, was realized the evaluation of the thermal treatment to determinate characteristics of heat penetration in the slower warming point (3,8 cm from base of can) finding the following results: fh = 19,34 minutes, jh = 0,46; Tpsih = 95,6°C, fc = 16,67 minutes, jc = 1,11 and Tpsic = 123,2°C; and the times of processing, by Stumbo method, to temperatures 104,4; 110; 115,6; 121,1; 126,7 and 132,2°C, being the times of processing 108,79; 54,76; 24,72; 13,77; 8,69 and 5,51 minutes, respectively, to obtain in all cases the same value of F121,1°C of 3,15 minutes.